Meta Analysis Study: Theory of Planned Behavior in Whistleblowing Intention - Handayani, Putri Fajar; Zusnita, Wa Ode (Universitas Bina Sarana Informatika, 2024)
Indonesia's Corruption Perception Index in 2022 had decreased significantly with a final score of 34 points and ranked Indonesia 110 out of 180 countries. It shows that corruption practices in Indonesia are high and the strategy for combating fraud is not effective. In practice, the fraud management strategies focus on improving internal control systems than preventive strategies such as whistleblowing system. This is due to the low intention of individuals to disclose fraud. Whistleblowers will encounter risks in organization, such as different prespective and norms in organization and the confidentiality and safety risk. Therefore, individuals need to carefully consider before deciding to become whistleblowers This study is aimed to examine individual factors that influence whistleblowing intention by the theory of planned behavior using meta-analysis technique, a quantitative method to measure the strength of the relationship of variables from previous research. Fourteen of the 53 selected studies were analyzed according to the eligibility criteria, the results is the highest correlation is the attitude toward behavior, then the subjective norm , and the lowest is the perceived behavioral control. It indicates that organization needs to stimulate an increase individual’s intention to disclose fraud by whistleblowing system as prevention strategy to combat fraud.